The Effect of Interpersonal Communication with Patient Satisfaction at the Pulo Brayan Health Center Dental Poly in 2023 - Rini Andayani; Masdalina Pane; Rosetty Sipayung (SEAN Institute, 2023)
Dental and oral hygiene is identified as an important factor in maintaining oral health. This importance is emphasized by government efforts, such as the provision of the dental clinics at Puskesmas (Community Health Centers). Dentist who work in dental clinic have a crucial role in providing care and its effects on patient satisfaction. Interpersonal communication between doctors and patients is a key factor in the success of treatment and in achieving patient satisfaction. The objective of this research is to analyze the effect of interpersonal communication on patient satisfaction at the dental clinic of Puskesmas Pulo Brayan in 2023. This is quantitative survey research design with a cross sectional approach. The number of samples is 93 people. The Data are collected using questionnaires and analyzed univariate, bivariate and multivariate analysis. The results of the research show that there is an effect of interpersonal communication dimension on patient satisfaction at Dentalt Clinic of Puskesmas Pulo Brayan in 2023 with the respect dimension (p-value = 0.005) OR = 4.557; empathy dimension (p-value = 0.001) OR = 5.614; audible dimension (p-value = 0.027) OR = 3.009; clarity dimension (p-value = 0.000) OR = 12.571; humble dimension (p-value = 0.009) OR = 3.600, and the most dominant dimension interpersonal communication dimension is the clarity dimension. It is recommended that the Puskesmas continue to improving its services in terms of interpersonal communication through training such as service excellence.